The effect of CYP2C19 gene polymorphisms on the pharmacokinetics and pharmacodynamics of prasugrel 5-mg, prasugrel 10-mg and clopidogrel 75-mg in patients with coronary artery disease - Gurbel, Paul A.; Bergmeijer, Thomas O.; Tantry, Udaya S.; ten Berg, Jurrien M.; Angiolillo, Dominick j.; James, Stefan; Lindahl, Tomas L.; Svensson, Peter; Jakubowski, Joseph A.; Brown, Patricia B.; Duvvuru, Suman; Sundseth, Scott; Walker, Joseph R.; Small, David; Moser, Brian A.; Winters, Kenneth J.; Erlinge, David (Thrombosis and Haemostasis, 2014)
CYP2C19 genotype has been shown to impact response to clopidogrel 75-mg but not prasugrel 10-mg. Here, we assessed effects of CYP2C19 metaboliser status on pharmacokinetics (PK) and pharmacodynamic (PD) responses to prasugrel 5-mg and 10-mg and clopidogrel 75-mg using data from two PK/PD studies in stable coronary artery disease (CAD) patients (GENERATIONS and FEATHER). Active metabolite concentrations (area under the curve, AUC[0-tlast]), maximum platelet aggregation (MPA) measured by light transmission aggregometry, vasodilator- stimulated phosphoprotein platelet reactivity index, and VerifyNow P2Y12-platelet reaction units (VN-PRU) were analysed by CYP2C19-predicted phenotype (extensive metaboliser [EM; N=154], *2-*8 non-carriers, vs reduced metaboliser [RM; N=41],*2-*8 carriers/* 17 non-carriers). AUC(0-tlast) was unaffected by metaboliser status for prasugrel 5-mg and 10-mg (geometric mean EM/RM ratios 1.00, 95% confidence interval [CI]: 0.86,1.17, p>0.99; and 0.97, 95% CI:0.85,1.12, p=0.71, respectively), but was lower among RMs receiving clopidogrel 75-mg (1.37, 95% CI:1.14,1.65, p<0.001). Platelet reactivity was not significantly affected by CYP2C19 metaboliser status for prasugrel 5-mg, or for prasugrel 10-mg by MPA and VNPRU, but for clopidogrel 75-mg was significantly higher in reduced metabolisers (all measures p<0.01). Prasugrel 10-mg showed greater antiplatelet effects vs clopidogrel 75-mg (all comparisons p<0.001). Prasugrel 5-mg showed greater antiplatelet effects vs clopidogrel 75-mg in RMs (all p<0.001), and comparable effects in EMs (all p≥0.37). In contrast to clopidogrel, prasugrel active metabolite PK was not influenced by CYP2C19 genotype. Antiplatelet effect for prasugrel 10-mg was greater irrespective of metaboliser status and for prasugrel 5-mg was greater for RMs and comparable for EMs as compared to clopidogrel 75-mg.
Keywords: Prasugrel; clopidogrel; CYP2C19; platelet reactivity; coronary artery disease